Centenary reflections on Mark Twain's No. 44, the mysterious stranger - Csicsila, Joseph, 1968-; Rohman, Chad, 1963- (University of Missouri Press, 2009)
"Collection of essays by accomplished Twain scholars examines Mark Twain's unfinished and last significant full-length work of fiction, No. 44, The Mysterious Stranger, attests to the importance of this late work, and addresses its significance as a culminating work on the nature of truth and the human condition"--Provided by publisher.